Effects of marketing claims on toddler food products on parents' product preferences, perceptions and purchasing intentions: an online experiment - Helen Gwenda Dixon; Mamaru Ayenew Awoke; Maree Scully; Jennifer McCann; Jane Martin; Belinda Morley; Anthea Rhodes; Alison McAleese; Andrea Schmidtke (BMC, 2024)
Abstract Background The retail market for toddler-specific packaged foods is growing. Many of these products are ultra-processed and high in nutrients of concern for health, yet marketed in ways that may make them appear wholesome. This study aims to assess parents' responses to claims on unhealthy, ultra-processed toddler food products and test whether removing such claims promotes more accurate product perceptions and healthier product preferences. Methods Parents of toddlers aged 12 to < 36 months (N = 838) were recruited for an online experiment testing four on-pack claim conditions: control (no claim); 'contains "good" ingredient'; 'free from "bad" ingredient'; and unregulated 'child-related' claim. Participants were randomly assigned to one condition, then viewed images of toddler food products that varied in nutrition content and the claims displayed. Participants completed tasks assessing product preferences (unhealthy product displaying claim vs. a healthier option with no claim, across four food categories (banana bars, strawberry snacks, blueberry yogurt snacks and veggie snacks)), purchase intentions and product perceptions. Poisson regression (count variable) and linear regression (continuous outcomes) analyses were employed to test for mean differences by marketing claim conditions. Results For the overall sample, brief exposure to 'free from "bad" ingredient' claims increased participant's intentions to purchase unhealthy food products for their toddlers, but there was no clear evidence that 'contains "good" ingredient' claims and 'child-related' claims significantly impacted parent's preferences, purchase intentions and perceptions of toddler foods. However, certain claims influenced particular parent subgroups. Notably, parents with three or more children chose more unhealthy products when these products displayed 'contains "good" ingredient' or 'free from "bad" ingredient' claims; the latter claims also promoted stronger purchase intentions and enhanced product perceptions among this subgroup. Conclusions Findings indicate that 'free from "bad" ingredient' claims on unhealthy toddler foods are of most concern, as they boost the appeal of these products to parents. 'Contains "good" ingredient' claims and 'child-related' claims showed limited effects in this study. Considering available evidence, we recommend claims should not be permitted on child-oriented foods, as they may promote inaccurate product perceptions and unhealthy product choices by parents, that can detract from their children's diets and health.